Calcareous nannofossil biomagneochronology of ODP Hole 122-762B (Tables 1, 2) - William G Siesser; Timothy J Bralower; Cheng Tang; Bruno Galbrun (PANGAEA, 1992)
Drilling on the Exmouth Plateau during Ocean Drilling Program Leg 122 recovered an almost complete Cenozoic sequence at Site 762. Sediments at this site contain abundant, diverse, and generally well-preserved calcareous nannofossils. The continuity of the stratigraphic sequence, preservation of the taxa, and availability of magnetostratigraphy offered an opportunity to construct a first-order biomagnetochronologic history for late Miocene-Quaternary calcareous nannofossils at Site 762. Magnetochronologically dated FADs/LADs for 23 different nannofossils are given in this study. FADs or LADs for five of these species (Discoaster blackstockae, D. calcaris, Rhabdosphaera claviger, R. longistylis, and R. procera) have never been presented before. In addition, a LAD for Ceratolithus rugosus is new. We believe these new age datums, and the complementary information on previous datums, will add to the growing refinement of Cenozoic biomagnetochronology.
Supplement to: Siesser, WG et al. (1992): Late Miocene-Quaternary calcareous nannofossil biomagnetochronology on the Exmouth Plateau, Northwest Australia. In: von Rad, U; Haq, BU; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 122, 677-681, https://doi.org/10.2973/odp.proc.sr.122.164.1992